Determination of the Effect of Humic Acid on Growth and Development Parameters of Parsley (Petroselinum sativum Hoffm.) Grown in Boron Soil - BOZKURT KOPUZ, ESİN; AKINCI, ŞENER (UNIV AGR SCI & VETERINARY MED CLUJ-NAPOCA, 2018)
Boron is an important micronutrient, required for all plant growth, and critical for high yield and quality of crops. The aim of the present research was to determine the effects of boron on pot-grown parsley (Petroselinum sativum Hoffm.). The experimental design consisted of four treatments using Hoagland-Arnon (1950) nutrient solutions with two different boron concentrations (B1 - 15 ppm and B2 - 150 ppm), each with and without 10 ml humic acid addition (HB1 and HB2), and controls with full strength Hoagland-Arnon solutions. Growth analyses of the parsley revealed that 15 ppm boron application caused an increase in root length leaf fresh and dry weight root fresh and dry weight and leaf area compared to control values. 150 ppm B (B2) concentration decreased all growth parameters compared to controls. The two humic acid treatments (HB1 and HB2) did not increase any of those growth parameters either in controls (C) or in the two boron (B1 and B2) concentrations. Analysis by (ICP-MS) revealed that B content in the leaves increased gradually in B1 and B2, as well as in both humic treatments where in HB2 it increased to 99.38% compared to B1. In the leaves, Mn, Zn and Fe contents behaved the same as B, increasing in all treatments, with the amounts in HB2 being significantly greater than in C, B1 and B2 leaves.
Keywords: boron; growth; humic acid; parsley; Petroselinum sativum; nutrient uptake; MINERAL-NUTRITION; PLANT-GROWTH; TOXICITY; DEFICIENCY; SUBSTANCES; ACCUMULATION; TRANSPORT; MOBILITY; WHEAT; ZINC